Case Series of Acute Myeloid Leukemia (AML) in Pregnancy – A Single Centre Experience over 5 years Review - Emily Christine D'Silva; Fann Rui Jeat; Lim Kar Koong; Jameela Sathar (USIM Press, 2024)
VOL. 9 NO. 1 (2023) Page (12-17)